Abrupt onset or exacerbation of anorexia nervosa following recent infections: a mini-review and a case report with an atypical manifestation of PANS - Lavalle Raffaele; Tournour Cristina; Rubano Serena; Delsedime Nadia; Panero Matteo; Abbate-Daga Giovanni (Eating and Weight Disorders)
Abstract Purpose This study examines the connection between infections and the abrupt onset or exacerbation of anorexia nervosa (AN) in the context of PANS (Pediatric Acute–Onset Neuropsychiatric Syndrome) and PANDAS (Pediatric Autoimmune Neuropsychiatric Disorders Associated with Streptococcal infections). Methods The authors conducted a literature review and present a case study of a 17-year-old girl treated at the University of Turin Eating Disorder Unit, whose AN presented with an abrupt onset following an infection and was characterized by a rapid and favorable course. Results The review includes 30 cases derived from six studies, suggesting that AN can manifest as PANS/PANDAS, with subjects, mainly adolescents, experiencing sudden or exacerbated eating restrictions alongside obsessive–compulsive behaviors. Some cases improved with antibiotics or standard psychiatric treatments, although age, symptom severity, and diagnostic markers like D8/17 varied across studies. Data on treatment follow-up also varied. The report refers to the case of V., a 17-year-old girl who developed AN following an intestinal infection. After significant weight loss and amenorrhea, she was hospitalized for 29 days, receiving psychiatric care, nutritional rehabilitation, and pharmacological treatment. Over 2 months of residential care and ongoing outpatient therapy, she improved notably, though mild body dysmorphophobia persisted. Conclusions While evidence suggests a possible link between infections and AN, research is still limited and inconsistent. Infections may trigger AN through autoimmune mechanisms or by initiating weight loss, particularly in younger patients. Although further studies are needed to clarify this relationship, infections should be considered in AN diagnosis, especially in pediatric cases. Level of Evidence: Level V, a narrative review and a case report.